Natural product extraction principles and applications - Rostagno, Mauricio A.; Prado, Juliana M. (RSC green chemistry series, 2013)
A comprehensive reference of the latest methodologies and techniques in the extraction and application of natural products. Presented within the philosophy of Green Chemistry.